Cedestis granadensis sp. nov., a new species from Spain (Lepidoptera, Yponomeutidae) - Zdenko Tokár; Friedmar Graf; Peter Huemer (Nota Lepidopterologica, 2024)
Cedestis granadensis sp. nov. is described from specimens taken in two localities in the Spanish province of Granada, in the highlands north of Puebla de Don Fadrique, and the mountains of Sierra de Huétor. The new species belongs to the genus Cedestis Zeller, 1839 in the family Yponomeutidae Stephens, 1829. It does not resemble any of the six other known species of this genus in external characters and it also differs significantly from species already barcoded according to the results of a DNA analysis. The immature stages of the new species are unknown. Colour photographs of the adults, the male genitalia, and of the habitat are included with an illustration of the female genitalia.